數學規劃講義final
數學規劃講義final
數學規劃講義final
x1 , x 2 ,…… , x n
d xi ≥0
z x1 , x 2 , … … , x n
z
CONVEXITY
λ x1 + (1 − λ ) x 2 ∈ S λ ∈ [0 , 1 ]
k ≥2 x1 , x 2 , … … , x k
λ 1 x1 + λ 2 x 2 + + λk xk
λ1 + λ2 + + λk = 1 λi ≥ 0 i = 1, 2 …, k
1 2,
x1 , x 2 , … … , x k
λ1 , λ 2 , , λ k ∈ ( 0 , 1)
C = {( x1 , x2 ) | x12 + x2 2 < 1}
{x ∈ n
| AX ≤ b}
{X ∈ n
| pX = k }or{X ∈ n
| p t X = k}
ℝⁿ
H + = {X ∈ n
| ppX > k } and H − = {X ∈ n
p < k}
| pX
ℝⁿ
ℝⁿ
S ⊂ conv(S )
k k
conv ( S ) = {∑ λi xi | { x1 , x2 , , xk } ⊂ S , λi ≥ 0, ∑ λi = 1}
i =1 i =1
x1 , x2 , , xk +1
x2 − x1 , x3 − x1 , , xk +1 − x1
conv ({ x1 , x 2 , , x k + 1 })
x ∈ conv ( S )
S1 + S2 = {x1 + x2 | x1 ∈ S1 , x2 ∈ S2 }
v1, v2 ,…, vk
k
C = { ∑ λ i v i | λ i ≥ 0 fo r i = 1 ,22 ,, k } .
i =1
v1, v2 ,…, vk
n
{(x1, x2 ,……, xn ) ∈ n
| ∑xi = 1 and xi ≥ 0 for i=1 2 …, n}
1,2,
i =1
.
S = {x ∈ n
| pi ⋅ x ≤ ai for i =1,2,…… ,m}
⇔ S = {x ∈ n
| A X ≤ b}
f 0 , f1 ,… , f d
∑ fi =1.1
(−1)
i =0
i
x1 , x 2 ,… , x k
d1 , d 2 ,… , d m
x ∈ S ⇔ x = ∑ i =1 λi xi + ∑ j =1α j d j
k m
x1 + x 2 + x 3 = 6 (1 )
x2 + x 4 = 3 (2 )
x1 ≥ 0 (3 )
⇒ x2 ≥ 0 (4 )
x3 ≥ 0 (5 )
x4 ≥ 0 (6 )
1 1 1 0
A= [ a1 a2 a3 a4 ] = ,
0 1 0 1
1 1 1 0
and d [ a1 a2 ] = , [ a1 a4 ] = ,
0 1 0 1
1 1 1 0
[ a2 a3 ] = , [ a2 a4 ] = ,
1 0 1 1
1 0
[ a3 a4 ] = are invertible
i tibl .
0 1
( a ) : (1) , ( 2 ) , & ( 5 ) , ( 6 )
1 1
∵ B = [a1 a 2 ] =
0 1
1 1 x1 6
⇒ =
0 1 x2 3
-1
x1 1 1 6 1 -1 6 3
⇒ x = 0 1 3 = 0
2 1 3 = 3
x1 3
x 3
⇒ 2 =
x3 0
x4 0
( b ) : (1) , ( 2 ) & ( 4 ) , ( 5 )
1 0
∵ B = [a1 a 4 ] =
0 1
1 0 x 1 6
⇒ =
0 1 x4 3
−1
x1 1 0 6 1 0 6 6
⇒ x = 0 1 3 = 0 1 3 = 3
4
x1 6
x 0
⇒ 2 =
x3 0
x4 3
( c ) : (1)
( ), ( 2 ) & (3), (5 )
1 0
∵ B = [a 2 a4 ] =
1 1
1 0 x2 6
⇒ 1 x = 3
1 4
−1
x2 1 0 6 1 0 6 6
⇒ x = 1 1 3 = -1 1 3 = -3
4
x1 0
x 6
⇒ 2 = , x = − 3( )
x3 0 4
4
x -3
1 1
( d ) : B = [a 2 a 3 ] =
1 0
1 1 x 2 6
⇒ =
1 0 x 3 3
−1
x2 1 1 6 0 -1 6 3
⇒ x = 1 0 3 = ( − 1) -1 1 3 = 3
3
x1 0
x 3
⇒ 2 =
x3 3
x4 0
1 0
( e ) : B = [a 3 a 4 ] =
0 1
1 0 x 3 6
⇒ =
0 1 x4 3
−1
x3 1 0 6 1 0 6 6
⇒ x = 0 1 3 = 0 1 3 = 3
4
x1 0
x 0
⇒ 2 =
x3 6
x4 3
3 6 0 0
3 , 0 , 3 , 0
Let d = (d1 , d 2 ,…… d n ) be a direction of S
and | d1 | + | d2 | + + | dn |= d1 + d2 + + dn = 1
Hence the set D = {d | Ad ≤ 0,
Hence, 0 ∑ i =1 di = 11, di ≥ 00, i = 11, 22,…, n}
n
In fact,
SIMPLEX METHOD
O
GEORGE BERNARD DANTZIG
((NOVEMBER 8,, 1914 – MAY 13,, 2005))
THE JOHN VON NEUMANN THEORY PRIZE HAS BEEN AWARDED
SINCE 1975
975. THE FIRST RECIPIENT GEORGE B. DANTZIG FOR
HIS WORK ON LINEAR PROGRAMMING.
Simplex Method
Min CX Min CX
subject to AX≤b subject to AX=b
X≥0 X≥0
, Find the extreme
extreme.
Here CX = C1 X1 + C2 X 2 + + Cn X n
H
is the objective function.
function
B b
−1
Suppose that we have a feasible solution X =
whose objective 0
B −1b
0 = CX = [C B N ] = C B B −1
b,
0
A = [B ]
where B is an m m basic matrix
and N is an m ((n-m)) nonbasic matrix.
Let X B and X N denote the set of basic
and
d nonbasic
b i variables
i bl ffor B.
B
Then X B ≥0 and XN ≥0 ,
X
b = A X = B N B = B X B + N X N
Moreover,, X
N
⇒ BX B = b − NX N
⇒ X B = B − 1b − ( B − 1 N ) X N
= B − 1b − ∑
j∈ R
( B − 1a j ) X j
=b− ∑
j∈ R
yjX j
w here b = B − 1b and y j = B − 1 a j
R is a current set of indices of the nonbasic variables.
Hence,,X B = b − ∑ y j X j ((1))
j∈ R
XB
Let C B C N = CB X B + CN X N
XN
B (b − ∑ y j X j ) + ∑ C j X j
j∈ R j∈ R
B ( B −1
b) − ∑ C B y j X j + ∑ C j X j
j∈ R j∈ R
0 − ∑ (C B y j − C j ) X j
j∈ R
0 − ∑ (Z j − C j ) X j (2)
j∈ R
Min 0 − ∑ ( Z j − C j )X j
j∈R
s.t. ∑ y j X j + X B = b
j∈R
Xj ≥ 0, j ∈ R
XB ≥ 0
( ) If Z j − C j ≤ 0 for
(1) f allll j R,
R
then the current basic solution
i the
is h optimal i l solution.
l i
solution
(2) If Zk −Ck > 0 for some k R,
then
h we can increase
i the
h value l off x k
0 Z = Z 0 − ( Z k − Ck ) X k , Z ↓ asX k ↑
Leaving variables?
X B b1 y1k
l
let X B = X Br = br − y rk xk (1)
X Bm b y mk
m
Z j − C j | j ∈ R} = Z k − C k (> 0)
(X k , X j = 0, j ≠ k )
X Br X k 0
(1 ) X Br 0
br
⇒ X k ↑ to , X Br ↓ to 0
y rk
X Br
bi br
X k = min 1≤ i ≤ m { | yik > 0} = >0
yik y rk
⇒ X Br !
br
⇒ X Br → 0 , X k →
y rk
If w e fin d a c o rre s p o n d in g n o n b a s ic
v a r i a b le X k w i t h Z k − C k > 0 ( X j = 0 , j ≠ k )
−1 −1
th e n X B = B b − (B N )X N = B -1 b − y k X k
B − 1b − y k
0 0
X
{ X =
B
= + X k | X k ≥ 0} ∈ S
X N 0 1
0 0
If y k ≤ 0 , then Z unboundness , Z → ∞
In fact
f , y k ≤ 0 iff Z unboundness.
b d
br bi
= m in
i 1≤ i ≤ m { | y ik > 0} m iinim
i all ratio
ti test.
t t
y rk y ik
(1) Xk , (2) X Br .
− yk
0
If yk ≤ 0 , is a recession direction of feasible region S.
1
0
yk > 0 ⇒ ∃yik > 0
− yk − yk
0 0
let d = ⇒ C • d = [C B C N ]
1 1
0 0
= ( − C B y k ) + C k = ( − Z k ) + C k < 0 ⇒ Z → −∞
The Simplex
p Method Algorithm
g
(Minimization Problem)
Initial Step: Choosing a starting basic feasible
solution(an extreme point of S)
Main Step:
(1)Solve BX B = b (X B =B-1b = b)
let X B = b = B −1b , X N = 0 and Z=C B X B =Z0
(2)Solve wB = CB (w = CB B −1 )
calculate wa j = c j = Z j − C j , j ∈ R
let Z k − Ck ≤ 0 , then STOP !
The current basic feasible solution is optimal.
Oth
Otherwise,
i GoG tot Step(3)
St (3) with
ith X k as the
th entering
t i variable.
i bl
(4) Let Xk enter the basis.
The
h iindex
d r off the
h variable
i bl X Br leaves
l the
h bbasis
i is
i
bi bi
determined by = min1≤i≤m{ | yik > 0}
yik yik
Update the basis B where ak replaces aBr
U d the
Update h iindex
d set R.
R
p Step(1).
Repeat p( )
Simplex Method in Tableau Format
s u b je c t to 1 i Z + 0 i X B + (C B X B N − C N ) X N = CBb
1i X B + ( B −1 N ) X N = B − 1b = b
−1
→ 1 0 C B B N − CN CB b
0 1 B −1 N B −1b = b
↓:
Z X Br ← ← XN → → RHS
Z 1 0 0 0 Z j − Cj Zk − Ck CB b
X B1 0 1 0 0 y1 j y1k b1
X Br 0 0 1 0 yrj yrk br
X Bm 0 0 0 1 ymj ymk bm
←:
Example :
Min x1 + x2 − 4x3 ⇒ Min x1 + x2 − 4x3 + 0x4 + 0x5 + 0x6
j to x1 + x2 + 2x3 ≤ 9
subject s.t. x1 + x2 + 2x3 + x4 =9
x1 + x2 − x3 ≤ 2 x1 + x2 − x3 + x5 =2
− x1 + x2 + x3 ≤ 4 − x1 + x2 + x3 + x6 = 4
x1 ≥0 xi ≥ 0 i = 1,2,3,4,5,6
x2 ≥0
x3 ≥ 0
1 1 2 1 0 0
A = [ a1 a 2 a3 a 4 a5 a 6 ] = 1 1 − 1 0 1 0
− 1 1 1 0 0 1
1 1 2 1 0 0
= [ N B ] , where
h N = 1 1 − 1 , B = 0 1 0
− 1 1 1 0 0 1
Z X4 X5 X6 X1 X 2 X 3 RHS
Z 1 0 0 0 −1 −1 4 0
X4 0 1 0 0 1 1 2 9
X5 0 0 1 0 1 1 −1 2
X6 0 0 0 1 −1 1 1 4
x1 0
x
2 0
x3 0
Starting point : = X 3 eneter, X 6 leave
x4 2
x 9
5
x6 4
4 0
2 0
Next step,change the column of X 3 : to be
−1 0
1 1
1 0 0
CB B = [ 0 0 0] 0 1 0 = [ 0 0 0]
−1
0 0 1
1 1 2 1 1 2
−1
B N = I 1 1 − 1 = 1 1 − 1
−1 1 1 −1 1 1
CB B N − CN = [ 0 0 0] − [1 1 − 4] = [ −1 − 1 4]
−1
The Two
Two--Phase Method
Phase1: Solve the following linear progam
g with the solution
starting
X = 0 and X a = b
Min 1 X a
s.t AX + X a = b
X ≥0
Xa ≥ 0
If the optimality X a ≠ 0 , then stop.
Otherwise,, let the basic and nonbasic variables to be X B and X N .
Phase2: Solve the following linear program
with feasible solution
−1
X B = B b and X N = 0
Min Z = C B X B + C N X N
−1 −1
s.t X B + B NX N = B b
XB ≥0
XN ≥ 0
E x : M in x1 − 2 x 2
s .t x1 + x2 ≥ 2
− x1 + x2 ≥ 1
x2 ≤ 3
x1 ≥ 0
x2 ≥ 0
⇒ x1 + x2 − x3 = 2
− x1 + x2 − x4 = 1
x2 + x5 = 3
x i ≥ 0 , i = 1, 2 , 3 , 4 , 5
1 1 −1 0 0
⇒ A = [a 1 a2 a3 a4 a 5 ] = − 1 1 0 −1 0
0 1 0 0 1
Phase1:
Starts by adding artificial variables x and x .
Min x6 + x7
s.t x1 + x2 − x3 + x6 =2
− x1 + x2 − x4 + x7 = 1
x2 + x5 =3
1 1 − 1 0 0 1 0
⇒ A = −1 1 0 − 1 0 0 1
0 1 0 0 1 0 0
Z x1 x2 x3 x4 x5 x6 x7 R .H .S
Z 1 0 0 0 0 0 -1 -1 0
x6 0 1 1 -1 0 0 1 0 2
x7 0 -1 1 0 -1 0 0 1 1
x5 0 0 1 0 0 1 0 0 3
⇓
Z x1 x2 x3 x4 x5 x6 x7 R .H .S
Z 1 0 2 -1 -1 0 -1 -1 3
x6 0 1 1 -1 0 0 1 0 2
x7 0 -11 (1 ) 0 -11 0 0 1 1
x5 0 0 1 0 0 1 0 0 3
⇓
Z x1 x2 x3 x4 x5 x6 x7 R .H .S
Z 1 2 0 -1 1 0 0 -2 1
x6 0 (2 ) 0 -1 1 0 1 -1 1
x7 0 -1 1 0 -1 0 0 1 1
x5 0 1 0 0 1 1 0 -1 2
⇓
Z x1 x2 x3 x4 x5 x6 x7 R .H .S
Z 1 2 0 -1 1 0 0 -2 1
x6 0 (2 ) 0 -1 1 0 1 -1 1
x7 0 -1 1 0 -1 0 0 1 1
x5 0 1 0 0 1 1 0 -1 2
⇓
Z x 1 x 2 x 3 x 4 x 5 x 6 x 7 R .H .S
Z 1 0 0 0 0 0 -1 -1 0
1 1 1 1 1
x 6 0 1 0 - 0 -
2 2 2 2 2
1 1 1 1 3
x 7 0 0 1 - - 0
2 2 2 2 2
1 1 1 1 3
x 5 0 0 0 1 - -
2 2 2 2 2
1
2
x
1
3
x 2 2
x 0
3
⇒ o p tim a l s o lu tio n : x 4 = 0
x 5
3
x 2
6
0
x 7
0
P h a s e 2 : M in Z − x1 + 2 x 2 + 0 x 3 + 0 x 4 + 0 x 5
Z x1 x 2 x 3 x 4 x 5 R . H .S
Z 1 -1 2 0 0 0 0
1 1 1
x1 0 1 0 - 0
2 2 2
1 1 3
x2 0 0 1 - - 0
2 2 2
1 1 3
x3 0 0 0 1
2 2 2
⇓
Z x1 x 2 x 3 x4 x5 R . H .S
1 3 5
Z 1 0 0 0
2 2 2
1 1 1
x1 0 1 0 - ( ) 0
2 2 2
1 1 3
x2 0 0 1 - - 0
2 2 2
1 1 3
x3 0 0 0 1
2 2 2
⇓
Z x1 x2 x3 x4 x5 R . H .S
Z 1 -1 0 0 0 -2 -6
x1 0 1 0 0 1 1 2
x2 0 0 1 0 0 1 3
x3 0 -1 0 1 0 1 1
x1 0
x2 3
⇒ x 3 = 1
x4 2
0
x 5
⇒ x1 − 2 x 2 = 0 − 2 ( 3 ) = − 6 i s t h e m i n i m u m .
Mi − x1 − 2 x2 + x3 − x4 − 4 x5 + 2 x6
E : Min
Ex
s.t x1 + x2 + x3 + x4 + x5 + x6 ≤ 6
2 x1 − x2 − 2 x3 + x4 ≤4
x3 + x4 + 2 x5 + x6 ≤ 4
x1 , x2 , x3 , x4 , x5 , x6 ≥ 0
⇒ x1 + x2 + x3 + x4 + x5 + x6 + x7 =6
2 x1 − x2 − 2 x3 + x4 +x8 =4
x3 + x4 + 2 x5 + x6 + x9 = 4
xi ≥ 0, i = 1, 2, 3, 4, 5, 6, 7,8, 9
1 1 1 1 1 1 1 0 0
⇒ A = 2 - 1 - 2 1 0 0 0 1 0
0 0 1 1 2 1 0 0 1
C = [- 1 - 2 1 - 1 - 4 2 0 0 0]
x1 0
0
x2
x3 0
x4 0
s ta r tin g b a s ic f e a s ib le s o lu tio n : x 5 = 0
x6 0
x 6
7
x8 4
4
x9
1 0 0
−1
B = a 7 a8 a9 = 0 1 0 = B
0 0 1
x7 x8 x9
Z 0 0 0 0
x7 1 0 0 6
x8 0 1 0 4
x9 0 0 1 4
z1 − c1 = 1, z 2 − c 2 = 2, z3 − c3 = − 1
z4 − c 4 = 1, z 5 − c 5 = 4 (* ), z6 − c6 = − 2
x7 x8 x9 x5 x7 x8 x9 x5
Z 0 0 0 0 4 Z 0 0 -2 -8 0
1
x7 1 0 0 6 1 ⇒ x7 1 0 - 4 0
2
x8 0 1 0 4 0 x8 0 1 0 4 0
1
x9 0 0 1 4 2 x9 0 0 2 1
2
Ite ra tio n 2 :
B = I 3 = B −1
x 7 x8 x 5
z 0 0 0 -8
x 7 1 0 0 4
x8 0 1 0 4
x 5 0 0 1 2
z1 − c1 = 1, z 2 − c 2 = 2 (* ), z 3 − c 3 = − 3
z 4 − c 4 = − 1, z 6 − c 6 = − 4 , z9 − c 9 = − 2
x 1
0
x 2 0
x
3 0
x 4
0
, C
N e w v e r te x : x 5 =
2 B = 0 0 - 2
x 0
6
x 7
4
x 4
8
x 0
9
x7 x8 x5 x2 x7 x8 x5 x2
z 0 0 0 -8 2 z -2 0 0 -1 6 0
x7 1 0 0 4 1 ⇒ x7 1 0 0 4 1
x8 0 1 0 4 -1 x8 1 1 0 8 0
x5 0 0 1 2 0 x5 0 0 1 2 0
Ite ra tio n 3 :
−1
B = I3 = B
x2 x8 x5
z 0 0 0 -1 6
x2 1 0 0 4
x8 0 1 0 8
x5 0 0 1 2
z 1 − c 1 = − 1, z 3 − c 3 = − 4 , z 4 − c 4 = − 2
z6 − c6 = − 5, z7 − c7 = − ?, z9 − c9 = − 1
Big-
Big
g-M Method
P: P( M ) :
Min CX Min CX + M i1i X a
s.t AX = b ⇒ s.t AX + X a = b
X ≥0 X ≥0
b≥0 Xa ≥ 0
where M is a sufficientily large positive real number.
number
Def:
Let S be a nonempty subset in R n .
Then the polar cone (dual cone ) of S,
denoted by S* ,is given by { p | px ≤ 0 for all x ∈ S} ≠ ∅.
Lemma:
Let A be a m × n matrix and let C = {A t y | y ≥ 0}
Then C* = { x | Ax ≤ 0 }
Farkas'' Lemma
Farkas
The Karush
Karush--Kuhn-
Kuhn-Tucker ((KKT))
conditions for inequality constraints:
Recall: (KKT)
The LP problem
oble (P) has
ha an
a optimal
o ti al solution
ol tio X,
X
if and only if,
c lies in the cone generated by
b the normal vector
ector
(gradient) of the binding constraints at X.
By KKT condition
condition,
the optimal solution X * of ( P ) must satisfy :
(1)AX ≥ b, X ≥ 0;
A
(2) [ w v ] =c, w ≥ 0, v ≥ 0;
I
(3) (AX b) 0 vX=0
(3)w(AX-b)=0, X 0
I
⇒ w * A X * + v * IX * = c X *
⇒ w *A X * = cX *
B y (1 ) , A X ≥ b ⇒ w A X ≥ w b , w ≥ 0
⇒ cX ≥ w A X ≥ w b, X ≥ 0
X *, w * ⇒ cX * = w *A X * = w *b
S in c e c X ≥ w A X ≥ w b , fo r w ≥ 0 , X ≥ 0
cX cX * , cX * = w *b X* (P ) .
wb w *b, cX * = w *b w *
(D ) .
Example 1:
Consider the following primal and dual problems.
( P ) Min 2x1 + 3x2 + 5 x3 + 2 x4 + 3x5
s.t. x1 + x2 + 2 x3 + x4 + 3 x5 ≥ 4
2 x1 − 2 x2 + 3 x3 + x4 + x5 ≥ 3
x1 ≥0
x2 ≥0
x3 ≥0
x4 ≥0
x5 ≥ 0
4
(D ) M ax [ w 1 w 2 ] = 4 w 1 + 3 w 2
3
1 1 2 1 3
s.t. [ w 1 w 2 ] ≤ [2 3 5 2 3 ]
2 -2 3 1 1
t
1 1 2 1 3
⇒ [w 1 w 2 ] ≤ [2 3 5 2 3 ]
t t
2 -2 3 1 1
1 2 2
1 -22 3
w
⇒ 2 3 1
≤ 5
w 2
1 1 2
3 1 3
⇒ 1w1 +2w 2 ≤ 2 ((*))
1w1 -2w 2 ≤ 3
2w1 +3w 2 ≤ 5
1w1 +2w 2 ≤ 2
3w 1 2 ≤3
3 1 +1w (*)
w1 ≥0
w2 ≥ 0
4 3
⇒ ( w1 , w 2 ) =(( , )
5 5
((run simplex
p method,, 1st 5th )
4 4 3
⇒ Max [ w1 w 2 ] =4w1 +3w 2 =4 × +3 × =5.
3 5 5
E xam ple2 :
n , j i a ij
(P ) M in c1 x1 + + cn xn
xj j ,cj j )
s .t . a11 x1 + + a1 n x n ≥ b1
a m 1 x1 + + a m n x n ≥ bm
x1 , x 2 , , , xn ≥ 0
: i bi
(D ) M ax b1 w1 + + bm w m w i i )
s .t . a11 w1 + + a m 1 w m ≤ c1
a 1 n w1 + + amn wm ≤ cn
w1 , w 2 , , , wn ≥ 0
: j cj
Game Theory
Theory
Th off Games
G anddEEconomici
Behavior-- published in 1944 by
Behavior
min max
max min
Nash Equilibrium.
Equilibrium
(Nash Equilibrium
Zero Sum Game ((Two Persons))
Ex:
(+2, −2) (+1.5, −1.5)
(+1.5, −1.5)
(+2.5, − 2.5)
(+2, −2) (+2, −2)
(+1,
1 −1) (+3,
( 3 − 3)
((10,10) ( , 25))
, ) (1,
(25,1)
(3,3)
(60, 60) (36, 70) (36, 35)
(70, 36) (50, 50) (30, 35)
(35,
(35 36) (35 (25, 25)
(35, 30) (25
N-Person Cooperative Game
Def: For each subset of N={1,2,ڮ,n},
{ , , , },
the characteristic function v of a game
gives amount v(S),
th th
then thatt numbers
b off S can b
be sure off receiving
i i
if they act together and form a coaliton
coaliton.
n
If X = ( X 1 , X 2 , " , X n ) , ∑X
i =1
i = v( N )
Question :
Sol :
v : 2{ , , }
\ {∅} → ℜ + ∪ {0}
({ }) = 0,, v({
v({ ({ }) = 0,, v({
({ }) = 0,, v({
({ }) = 0,,
v({ , }) = 0, v({ , }) = ( 2 − p ) + ( p − 1) = 1,
( p ⇒ 1 ≤ p ≤ 2,
2 : 2 − p,
p : p − 1)
v({ , }) = ( 2 − p ) + ( p − 1) = 1
v{( , , )} = 1 ( )
( x1 , x 2 , x 3 ) ⇒ x1 + x 2 + x 3 = v{(
{( , , )} = 1
x1, x 2 ,x 3 ≥ 0
x 1 + x 2 + x 3 = v{ ( , , )} = 1
x 1 + x 2 ≥ v ({ , }) = 1
x 1 + x 3 ≥ v ({ , }) = 1
x 2 + x 3 ≥ v ({ , }) = 0
x 1 ≥ v ({ }) = 0
x 2 ≥ v ({ }) = 0
x 3 ≥ v ({ }) = 0
⇒ s o l u t i o n (1 , 0 , 0 ) :
Def: The core of an n-person game (N,v)
is the set C(
C(N,
N,vv) satisfies
∑ i∈ s
X i ≥ v ( S ), ∀ S ⊂ N , S ≠ ∅
∑X
i =1
i = v( N ), X i ≥ v(i), ∀i ∈ N ,
S ap ey Va
Shapley Value
ue
Given any n-person game with the characteristic function v,
define v(
=)0
0, there is a unique vector X = ( x 1 , x 2 , " , x n ),
(n − k )!
w ith X i = ∑S n!
[ v ( S ) − v ( S \ {i})], k = | S |
i∈ S
1
∑
S n −1
[ v ( S ) − v ( S ) \ {i})]
i∈ S
k − 1
=
n
1
= ∑
S n −1
[ v ( S ) − v ( S ) \ {i})], | S |= k = 1, 2, " , n .
i∈ S n
k − 1
LLOYD SHAPLEY
( SHAPLEY WON THE 2012 NOBEL MEMORIAL PRIZE IN
ECONOMIC SCIENCES ). WON THE JOHN VON
NEUMANN THEORY PRIZE IN 1981
1981.
EX :
N= ={1,2}
{1 2}
v(1,2) = 1, v(2) = 0, v(1) = 0
(2 −1)!(1−1)! (2 − 2)!(2 −1)!
X1 = [v(1) − v(∅)] + [v(1,2) − v(2)]
2! 2!
1 1 1
= (0 − 0) + (1− 0) =
2 2 2
1
X2 =
2
Sol :
X = ( X B , X G , X O , X C ), N = ( B , G , O , C )
v(B,G ) = v(B,O ) = v(B,C )
= v(B,G ,O ) = v(B,G ,C )
= v(B,O , C ) = v(B, G ,O ,C )
= 1( )
h e r w iise , v ( S ) = 0
O th
XB
(4 − 2)!(2 −1)!
= {[v(B, G) − v(G)] + [v(B, O) − v(O)] + [v(B, C) − v(C)]}
4!
(4 − 3)!(3 −1)!
+ {[v(B, G, O) − v(G, O)] + [v(B, G, C) − v(G, C)] + [v(B, O, C) − v(O, C)]}
4!
(4 − 4)!(4 −1)!
+ [v(B, G, O, C) − v(G, O, C)]
4!
2 3 1
= + =
12 12 2
1
XG = XO = XC =
6
1 1 1 1
⇒ X = ( XB , XG , XO , XC ) = ( , , , )).
2 6 6 6
Ex: (Airport Pricing)
S l:
Sol
N ={ , , }
v (∅ ) = 0, v ( ) = −100, v ( ) = v ( , ) = − 150
v( ) = v( , = v( , ) = v( , , ) = −400
⇒ ϕ ( N , v ) = (ϕ (v )), ϕ (v )), ϕ (v ) )
200 350 1850
= − ,− ,−
6 6 6
X : X : X = 4 : 7 : 37